2010
DOI: 10.1002/mnfr.201000329
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavone genistein induces cell death in breast cancer cells through mobilization of endogenous copper ions and generation of reactive oxygen species

Abstract: As copper levels are known to be considerably elevated in almost all types of cancers, in this proof-of-concept study we show that genistein is able to target endogenous copper leading to prooxidant signaling and consequent cell death. We believe that such a mechanism explains the anticancer effect of genistein as also its preferential cytotoxicity towards cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 27 publications
6
68
0
Order By: Relevance
“…13 Dietary genistein has also been reported to reduce chemical-induced prostate cancer 14 and colon cancer 15,16 in rats. In vitro studies conducted in different cancer cell lines confirmed that by affecting various cellular targets, including several critical tumor suppressor genes, genistein treatment repressed cancer cell proliferation, [17][18][19] induced apoptosis [19][20][21] and led to cell cycle arrest. [22][23][24] However, the mechanism behind the ability of genistein to modulate the expression of tumor-promoting and tumor-suppressing genes during cancer development remains unclear.…”
Section: Genistein An Epigenome Modifier During Cancer Preventionmentioning
confidence: 90%
“…13 Dietary genistein has also been reported to reduce chemical-induced prostate cancer 14 and colon cancer 15,16 in rats. In vitro studies conducted in different cancer cell lines confirmed that by affecting various cellular targets, including several critical tumor suppressor genes, genistein treatment repressed cancer cell proliferation, [17][18][19] induced apoptosis [19][20][21] and led to cell cycle arrest. [22][23][24] However, the mechanism behind the ability of genistein to modulate the expression of tumor-promoting and tumor-suppressing genes during cancer development remains unclear.…”
Section: Genistein An Epigenome Modifier During Cancer Preventionmentioning
confidence: 90%
“…3,4 Genistein (4′,5,7-trihydroxyisoflavone, Figure 1) is one of the most abundant and best studied soy isoflavones and has received great attention for its many physiological functions, including potential antitumor activity. 5,6 Recent studies have indicated that genistein could inhibit tumor cell growth and proliferation, arrest cell cycle at G2/M phase, suppress tumor migration, invasion, and angiogenesis, and induce apoptosis and autophagocytosis. [7][8][9][10][11] However, the clinical use of genistein for cancer therapy was hindered by its poor water solubility and oral bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…These beneficial effects are considered to be particularly manifest in the lower risk of breast cancer reported for Asian women who consume soy-based foods as part of their regular diets beginning in early life (Korde et al 2009;Dong and Qin 2011). We Dave et al 2005;Su and Simmen 2009;Simmen 2010, 2011;Montales et al 2012) and others (Ullah et al 2011;Anastasius et al 2009;Kazi et al 2003;Vinall et al 2007) have shown that specific bioactive components of soy foods function by regulating cellular networks and pathways that promote apoptosis, inhibit proliferation, induce differentiation, and suppress inflammation, to collectively hinder tumor development and growth.…”
Section: Introductionmentioning
confidence: 99%